Inclusive growth and development in the 21st century : a structural and institutional analysis of China and India - Dutta, Dilip (Series on economic development and growth, 2014)
Using case studies of both China and India, this book reinforces the fact that the processes of economic growth and development are dynamic and organic in the sense that structural and institutional elements are not only interrelated, but also constantly changing in their patterns of interactions - more so during the transitional period of both countries. Inclusiveness or its lack in some specific socio-economic sector/context, geographical region/state or economy as a whole is critically analysed, using recent data on both the countries from different sources.